Attitude as a correlate of utilization of information communication technology in instructional delivery among social studies teachers in Oyo State (2016)
This study investigated the relationship that existed between attitude and ICT utilization level of Social Studies teachers in secondary schools. The study adopted descriptive survey research. A validated questionnaire was used to collect data from 198 respondents drawn from ninety private and public junior secondary schools in Oyo State using multi stage sampling technique. The data collected was analyzed using inferential statistics of Pearson Product Moment Correlation PPMC and t-test at 0.05 level of significance. The study revealed that teachers' attitude towards ICT have a positive but low correlation with ICT utilisation (r = 0.217; N= 198); there was no significant difference between the attitude of male and female teachers towards utilisation of ICT in secondary schools (t(196) = 1.968; D = 0.138); there no significant difference between the ICT utilization ofmale and female teachers in secondary school (t (196) = 0.423; p>0.05; D=0.030). Recommendations were directed toward government assistance in equipping schools with adequate facilities and effective monitoring of schools; ICT use for instructional delivery should be given greater consideration than it currently receives among others.